1998
DOI: 10.1111/j.1651-2227.1998.tb01549.x
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte superoxide dismutase activity and plasma malondialdehyde levels in children with Henoch Schönlein purpura

Abstract: Demircin G, Ö ner A, Ü nver Y, Bülbül M, Erdogan Ö . Erythrocyte superoxide dismutase and plasma malondialdehyde levels in children with Henoch Schönlein purpura. Acta Paediatr 1998; 87: 848-52. Stockholm. ISSN 0803-5253 Reactive oxygen molecules (ROM) have been suggested to contribute to many pathological conditions including vasculitides and renal diseases. In the present study we measured the activity of superoxide dismutase (SOD) as an antioxidant enzyme in red blood cells and the level of malondialdeh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…Involvement of oxidative stress and reactive oxygen molecules (ROMs) in HSP is more indirect evidence for the role of apoptosis in HSN pathogenesis. Besides, ROM levels are under the control of the Bcl-2 gene product (20,21). The mainly tubular expression of bax and bcl-2 in our patients is in agreement with the literature (18,22).…”
Section: Discussionsupporting
confidence: 92%
“…Involvement of oxidative stress and reactive oxygen molecules (ROMs) in HSP is more indirect evidence for the role of apoptosis in HSN pathogenesis. Besides, ROM levels are under the control of the Bcl-2 gene product (20,21). The mainly tubular expression of bax and bcl-2 in our patients is in agreement with the literature (18,22).…”
Section: Discussionsupporting
confidence: 92%
“…Despite the existence of various experimental studies concerning oxidant injury in vascular diseases [6,7], few clinical studies evaluated the role of oxidative injury in the pathogenesis of vasculitis [9,10]. In this study, we investigated the role of neutrophil activation and protein oxidation (thiol stress) in the pathogenesis of HSP by measuring serum enzyme activity of MPO as a marker of neutrophil activation and total free thiol groups as a marker of protein oxidation together with serum antioxidant enzyme ARYL activity, serum TOS, and CLP levels.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism has a crucial and probably causative role in the pathogenesis of various acute and chronic diseases, including inflammation, renal failure, and cardiovascular damage [3][4][5]. Experimental studies on oxidative injury have been carried out in glomerular diseases and vasculitis [6][7][8]; however, clinical investigations on oxidative stress in HSP are scarce [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…If the oxidative damage is excessive, SOD will also be expected to increase for the compensation and protection of tissue injury. [23] Thus, the lack of increase in acute stage SOD activity may be due to some depletion resulting from oxidative stress as detected by higher MDA levels. Sustained SOD activity in acute stage of AGN suggested that antioxidant defense mechanisms work well in these patients; antioxidant enzymes were not totally depleted and remained at a steady state as a compensation for protection from hazardous effects of increased ROS.…”
Section: Discussionmentioning
confidence: 99%